In vitro antiparasitic activity of microbial pigments and their combination with phytosynthesized metal nanoparticles. Issue 5 (October 2015) - Rahul, Suryawanshi; Chandrashekhar, Patil; Hemant, Borase; Bipinchandra, Salunke; Mouray, Elisabeth; Grellier, Philippe; Satish, Patil
Abstract: Bioactive pigments were extracted and purified from cultures of Serratia marcescens and Chromobacterium violaceum . Spectroscopic, FTIR, and HPLC analyses showed prodigiosin and violacein as the principle molecules in the extract. Bioactive microbial pigments prodigiosin, violacein and their combinations with phytosynthesized silver and gold nanoparticles were studied for in vitro growth inhibition of Plasmodium falciparum and Trypanosoma brucei gambiense . Prodigiosin was found to be more effective than violacein for inhibition of both parasites in vitro. Specifically, combinations of the microbial pigment prodigiosin with metal nanoparticles showed a significant decrease in the IC50 values on both parasites (2.7 to 3.6 fold) without increase of cytotoxicity upon mammalian cells. The data may be useful for the microbial pigment based drug designing. Graphical abstract: Highlights: Prodigiosin with nanoparticles reduces IC50 s by 2.7 to 3.6 fold against both parasites. Prodigiosin is effective than violacein for parasite inhibition in vitro. Prodigiosin and violacein are nontoxic to tested mammalian cells.